Pregnancy in ankylosing spondylitis: the view of a female patient and a physician - Z. M. Gandaloeva; O. A. Krichevskaya; S. I. Glukhova; T. V. Dubinina; A. M. Lila (Современная ревматология)
Objective: to study the impact of the diagnosis of ankylosing spondylitis (AS) on the planning of pregnancy by patients and their attitude towards the use of drugs during gestation and to assess the competency of physicians in the issues relating to pregnancy in AS.Patients and methods. The data of three studies based on the questionnaire surveys of female AS patients and rheumatologists.Results and discussion. The questionnaire survey revealed a decline in the number of pregnancies per woman after the onset of AS. Having learned about their diagnosis, 70% of patients reported a change in their maternity plans; however, most (80%) women said that they were still going to become pregnant, but they would constantly feel discomfort and fear for their own health and the health of their future child. Pregnancy was rejected due to AS development by 13.9% of patients, regardless of the presence or absence of children born in the healthy period of their life. Only 50% of women discussed the issues relating to pregnancy with a rheumatologist, and one third of them did not obtain the necessary information. Only one fourth of patients were ready to continue treatment for AS in the period of preparation for conception and during gestation.On the whole, Russian rheumatologists have enough knowledge about pregnancy outcomes in AS, and, in particular, about the factors which may influence the favorable outcome and about the fundamentals of follow-up for pregnant women. At the same time, 18% of rheumatologists expect increased AS activity during gestation, more than two thirds consider sacroiliitis to be an indication for surgical delivery, and 30% are ready to discontinue the drugs which are permitted for use before pregnancy.Conclusion. Lack of information about the planning and course of pregnancy in AS, the risk of disease exacerbation and the safety of therapy during gestation is noted in both patients and rheumatologists. It is necessary to implement educational measures on the problem of pregnancy in AS for rheumatologists and women of fertile age and their family members.